Optimized fabrication of BiOBr/TiO2 nanotube arrays for efficient degradation of organic pollutant under visible light irradiation. Issue 2 (April 2021) - Ma, Bingrui; Xin, Shuaishuai; Xin, Yanjun; Ma, Xiaoming; Zhang, Chunlei; Gao, Mengchun
Abstract: The BiOBr modified TiO2 nanotube arrays (BiOBr/TNAs) heterojunctions were fabricated through anodic oxidation followed by successive ionic layer adsorption and reaction method. The optimum synthetic parameters of BiOBr/TNAs were obtained by the response surface methodology. The surface structure analysis showed that BiOBr nanoflakes were successfully deposited on the surface of TNAs and formed BiOBr/TNAs heterojunctions. The BiOBr/TNAs displayed higher visible light absorption property than bare TNAs due to the intrinsic visible light response of BiOBr and excellent light-scattering property of the formed heterostructure. The photoelectrochemical properties and photoluminescence spectra analysis revealed that an appropriate loading amount of BiOBr on the TNAs could effectively enhance photoconversion efficiency and the separation of photogenerated electron-hole pairs. The photocatalytic degradation efficiency of Rhodamine B (Rh B) by the optimum BiOBr/TNAs reached almost 85% under visible light irradiation, which was much higher than that of bare TNAs (less than 20%). The radical scavenging experiments and electron spin resonance spectra suggested that ·O2 – and h + played crucial roles in the photocatalytic degradation of Rh B. The possible mechanism and degradation pathways of Rh B by BiOBr/TNAs were proposed under visible light irradiation. Graphical Abstract: ga1 Highlights: BiOBr modified TiO2 nanotube arrays (BiOBr/TNAs) heterojunctions were synthesized. The optimum synthetic parameters were obtained by response surface methodology. BiOBr/TNAs heterojunctions reduced the recombination of electron-hole pairs. BiOBr/TNAs exhibited higher photocatalytic activity under visible light irradiation.